Spiritualitas Persaudaraan Universal: Belajar dari Kisah Orang Samaria yang Baik Hati (Lukas 10:25-37) - Kristiyanto, Nikolas (Sanata Dharma University, 2023)
Humans can never live alone, but they will always need other people in their lives. Human philosophy calls this intersubjectivity. Humans are always part of a larger community than just themselves. It is not surprising that Aristotle said that humans cannot live in isolation. From here, Christian ethics guides us that respecting others is part of our faith and that our fellow human beings are equal creations of God – not limited by any criteria created by humans. However, Jesus demanded more from His followers. Not only to understand